2017
DOI: 10.1007/s40596-017-0864-4
|View full text |Cite
|
Sign up to set email alerts
|

Residents Teaching Residents: Results of an Interdisciplinary Educational Endeavor

Abstract: Collaborative, interdisciplinary care is complex and its benefits can be difficult to assess. Data from this study showed that interdisciplinary teaching at the resident level has the potential to be an effective means for building collaboration and can lead to a subjective improvement in comfort managing common inpatient psychiatric presentations on medical wards. Additionally, qualitative observations suggest that such an intervention can improve interdisciplinary collaboration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Peer feedback has been explored in obesity intervention 17 and use of peer versus expert standards have been studied in feedback during laparoscopic training. 18 In 2017, Warren et al 19 showed that resident to resident teaching on the wards improved the comfort level of internal medicine residents on inpatient service. The concept of a resident as a peer surgical coach has yet to be studied in resident education in the simulation lab and there are no studies that directly compare expert coaching with peer coaching in the surgical setting.…”
Section: Introductionmentioning
confidence: 99%
“…Peer feedback has been explored in obesity intervention 17 and use of peer versus expert standards have been studied in feedback during laparoscopic training. 18 In 2017, Warren et al 19 showed that resident to resident teaching on the wards improved the comfort level of internal medicine residents on inpatient service. The concept of a resident as a peer surgical coach has yet to be studied in resident education in the simulation lab and there are no studies that directly compare expert coaching with peer coaching in the surgical setting.…”
Section: Introductionmentioning
confidence: 99%
“…As the psychiatrist shortage worsens, psychiatrists may be increasingly expected to teach non-psychiatric physicians how to administer quality psychiatric care. However, few teaching curricula or extracurricular programs have focused on psychiatrists’ roles as interdisciplinary educators [ 3 , 4 ]. These two previous studies assessed cross-sectional learning outcomes of non-psychiatric physicians rather than the longitudinal process of developing psychiatry residents as educators.…”
mentioning
confidence: 99%
“…Peer-to-peer initiatives were evaluated by Warren et al [17], Chaffkin and Wasser [18], and Huzij et al [19]. In Warren et al [17], psychiatry residents created and delivered five interactive lectures to a rotating group of internal medicine residents, the latter of whom reported both increased knowledge and skill on all psychiatric topics presented.…”
mentioning
confidence: 99%
“…Peer-to-peer initiatives were evaluated by Warren et al [17], Chaffkin and Wasser [18], and Huzij et al [19]. In Warren et al [17], psychiatry residents created and delivered five interactive lectures to a rotating group of internal medicine residents, the latter of whom reported both increased knowledge and skill on all psychiatric topics presented. In Chaffkin and Wasser [18], a psychiatry resident created and implemented a 1-h didactic session for a total of 20 internal medicine residents who completed both pre-and postcurriculum surveys.…”
mentioning
confidence: 99%